Empathic communication training for cadres in assisting families of stunting toddlers - Puput Mariyati; Denis Melati; Nining Tyas Triatmaja (Priviet Social Sciences Journal, 2025)
Posyandu cadres are the spearhead of real Community Health Center services in helping to address nutritional problems in the community. To support their role, Posyandu cadres must possess adequate communication skills to convey nutrition and health messages in a simple manner. Cadres are required to listen actively, non-judgmentally, respond empathetically, understand emotions, and create a comfortable atmosphere for those receiving nutritional assistance, ensuring optimal intervention. Empathetic communication training is an effort to improve the cadres' abilities to support families of stunted toddlers. This study uses a quantitative approach with a one-group pretest-posttest experimental design method, which aims to determine the effect of empathic communication training in improving the knowledge and skills of Posyandu cadres in assisting families with malnutrition. This study involved 20 participants from the village cadres distance Plosoklaten Kediri. Conducting given is empathic communication training that contains material about the process of empathic communication and empathic communication practice roleplay. Understanding of the training material was measured using questionnaires made by researchers who describe the role of cadres, concepts, and processes of empathic communication, as well as scenarios containing cases for practicing empathic communication. Hypothesis testing using a paired samples t-test with p value = 0.001 (p<0.05). There is a significant difference in the level of knowledge between before and after being given empathic communication training for Posyandu cadres.